75.9k views
11 votes
3.(x + 2) + (2x + 3) = 23


2 Answers

6 votes

Answer:

x = 6

Explanation:

1. Remove parentheses where unneeded. x + 2 + 2x + 3 = 23

2. Add constants. x + 5 + 2x = 23

3. Combine like terms. 3x + 5 = 23

4. Subtract "5" from the constants on both sides of the equation. 3x = 18

5. Divide both sides by 3. 3x/3 = 18/3

6. Simplify. x = 6

User Bartosz Milewski
by
6.2k points
2 votes

Answer:

x = 6

Explanation:

(x + 2) + (2x + 3) = 23

Combine like terms

3x +5 = 23

Subtract 5 from each side

3x+5-5 = 23-5

3x = 18

Divide each side by 3

3x/3 = 18/3

x = 6

User CCates
by
4.9k points